Molecular characterization of field isolates of Avian Infectious Laryngeotracheitis Virus from different farms in Iraq: Aida Bara Allawe1, Amer Abdulameer Abbas2, Zaid Haddam Taha1 and Shony M. Odisho1 - Allawe, Aida Bara (The Iraqi Journal of Veterinary Medicine, 2017)
This study was conducted to detect virulent isolates of avian infectious laryngeotracheitis virus in Iraq by Real Time-Polymerase Chain Reaction with the amplification of glycoprotein G gene which is responsible for virulence of the virus. Seventy samples (larynx and trachea) were collected from different farms in Iraq to investigate presence of avian infectious laryngeotracheitis virus (detection of virulent isolates from other vaccine strains). Five samples out of seventy samples were virulent isolates (positive result) by using Real Time-Polymerase Chain Reaction utilizing flurescein amidite labeled probe specific for detection of isolates that have G gene (by amplification of G gene) for the first time in Iraq. These virulent isolates were negative by using Real Time-Polymerase Chain Reaction utilizing Quasar-labeled probe specific for the detection of attenuated isolates that lack G gene and targeted a region within glycoprotein J downstream from the sequence of glycoprotein G.